Volume 4: Cycle Innovations; Cycle Innovations: Energy Storage 2022
DOI: 10.1115/gt2022-83424
|View full text |Cite
|
Sign up to set email alerts
|

The Design of a Small-Scale Pumped Heat Energy Storage System for the Demonstration of Controls and Operability

Abstract: Long-duration, grid-scale energy storage technologies provide a potential pathway to enable the full penetration of renewables into the electricity grid while still maintaining grid reliability and security. Among these technologies, pumped heat energy storage (PHES) stores energy thermally using a heat pump and discharges that stored thermal energy with a heat engine when needed. With high potential system performance, implementation versatility, and no geological and geographical constraints, PHES is a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Further work is then required to assess the magnitude of these issues and to investigate whether possible solutions may negatively affect the start-up time of the plant, therefore nullifying the economic effort of using more sophisticated heat exchangers. Finally, it is worth mentioning that the considered Brayton heat pump showed a start-up time consistent with the ones reported for a similar cycle specifically designed for energy-storage purposes [17], where start-up times in the 1.38−2 h range have been reported depending on the opening the compressor recycle valve opening. Here, differences in the results may be due to the different designs of the components, operating modes, temperature levels, and heat exchangers' size or technology, as the system are meant for different purposes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further work is then required to assess the magnitude of these issues and to investigate whether possible solutions may negatively affect the start-up time of the plant, therefore nullifying the economic effort of using more sophisticated heat exchangers. Finally, it is worth mentioning that the considered Brayton heat pump showed a start-up time consistent with the ones reported for a similar cycle specifically designed for energy-storage purposes [17], where start-up times in the 1.38−2 h range have been reported depending on the opening the compressor recycle valve opening. Here, differences in the results may be due to the different designs of the components, operating modes, temperature levels, and heat exchangers' size or technology, as the system are meant for different purposes.…”
Section: Discussionsupporting
confidence: 82%
“…Despite not optimizing the gas turbine speed ramp for quick start-ups, a start-up time of around 30 min was reported. Smith et al [17] presented the design of a laboratory scale pumped thermal electricity storage demonstration plant in order to test the control strategies and demonstrate the system operability and criticalities. Start-up times of around 1.38 h and 2 h were reported depending on the compressor recycle valve opening.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the heat flow rate transferred through the heat exchanger was determined based on the ε-NTU method [18], summarized in Equation (11):…”
Section: Heat Exchangersmentioning
confidence: 99%
“…Zühlsdorf et al [10] suggested that technically and economically feasible heat pumps capable of supplying heat up to 280 • C could be developed by leveraging equipment already available in the oil and gas industry. Under this approach, various concepts aiming to supply heat at temperatures higher than 150 • C have been put forward in the literature for industrial and energy storage applications [5,11]. However, these systems need to be developed, realized, and integrated into relevant industries.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Several concepts capable of delivering heat above 150 °C have been proposed in the literature for industrial purposes [5]. Further prototypes have also been proposed for energy storage applications [10]. Nevertheless, these heat pumps must be developed, built, and integrated into the relevant industries.…”
Section: Introductionmentioning
confidence: 99%